Modified-BEP Chemotherapy in Patients With Germ-Cell Tumors Treated at a Comprehensive Cancer Center. (June 2020) - Aurilio, Gaetano; Verri, Elena; Frassoni, Samuele; Bagnardi, Vincenzo; Cossu Rocca, Maria; Cullurà, Daniela; Milani, Martina; Mascia, Roberta; Curigliano, Giuseppe; Orsi, Franco; Jereczek-Fossa, Barbara A.; Musi, Gennaro; et al.
Abstract : Objectives: Bleomycin, etoposide, and cisplatin (BEP) is the most common and successful chemotherapy regimen for germ-cell tumor (GCT) patients, accompanied by a bleomycin-induced dose-dependent lung toxicity in certain patients. In an attempt to reduce bleomycin-toxicity, we developed a modified-BEP (mBEP) regimen. Materials and Methods: Between August 2008 and February 2018, 182 unselected mainly testicular GCT patients (39 with adjuvant purpose and 143 with curative purpose) received a tri-weekly 5-day hospitalization schedule with bleomycin 15 U intravenous (IV) push on day 1 and 10 U IV continuous infusion over 12 hours on days 1 to 3, cisplatin 20 mg/m 2 IV, and etoposide 100 mg/m 2 IV on days 1 to 5. Pulmonary toxicity was assessed through chest computed tomography scan and clinical monitoring. Results: Median number of mBEP cycles was 3 (range: 1 to 4). In the curative setting, according to the International Germ Cell Cancer Collaborative Group (IGCCCG) prognostic system, 112, 21, and 9 patients had good-risk, intermediate-risk, and poor-risk class, respectively; 66 (46%) patients had complete response (CR), 67 (47%) had partial response (52 of whom became CR afterwards), 6 (4%) had stable disease (that in 3 became CR afterwards), 3 (2%) progressed, and 1 (1%) died of brain stroke. At a median follow-up of 2.67 years (interquartile range: 1.23-5.00 y), 1 and 5-year overall survival and progression-free survival were 99% and 95%, and 90% and 88%, respectively. In the entire patient population, there was grade 3/4 neutropenia in 92 patients (51%), febrile neutropenia in 11 patients (6%), grade 1/2 nausea in 74 patients (41%), and no death due to pulmonary toxicity. Conclusion: In GCT patients, our mBEP-schedule would suggest an effective treatment modality without suffering meaningful pulmonary toxicity.